Effect of Hydrosoluble Chlorine–Mediated Antimicrobial Photodynamic Therapy on Clinical Parameters and Cytokine Profile in Ligature‐Induced Periodontitis in Dogs. Issue 6 (1st June 2013) - Sorkhdini, Parand; Moslemi, Neda; Jamshidi, Shahram; Jamali, Raika; Amirzargar, Ali Akbar; Fekrazad, Reza
Abstract : Background: Recently, a hydrosoluble chlorine composed of sodium salts chlorine e6, chlorine p6, and purpurine‐5 has been shown to be a promising photosensitizer in antimicrobial photodynamic therapy (aPDT). The aim of this study is to evaluate the effects of adjunctive application of hydrosoluble chlorine–mediated aPDT compared with scaling and root planing (SRP) alone on clinical parameters and cytokine levels in gingival crevicular fluid of dogs with experimental periodontitis. Methods: Periodontal disease was induced by placing silk ligatures around both maxillary and mandibular teeth. After establishment of attachment loss, full‐mouth SRP was performed in all dogs. One day after SRP, each quadrant randomly received one of the following treatment modalities: hydrosoluble chlorine plus diode laser (wavelength 662 nm, power 100 mW, continuous mode, time of irradiation 20 seconds), hydrosoluble chlorine alone, laser alone, or no adjunctive treatment. The same adjunctive procedure was repeated 1 week later. Clinical parameters including periodontal probing depth, clinical attachment level, and bleeding on probing, as well as crevicular levels of interleukin‐1β and tumor necrosis factor‐α, were evaluated at baseline, at 3 weeks, and at 3 months after treatment. Results: After both 3 weeks and 3 months, all treatment groups showed significant improvement in all clinical and immunologic parameters ( P <0.001). No significant differences were found between the four groups with regard to the measured parameters ( P >0.05). Conclusion: Based on the results of this study, adjunctive use of hydrosoluble chlorine–mediated aPDT with the current setting has no additional effect on the clinical parameters or proinflammatory cytokine levels in ligature‐induced periodontitis.